2020
DOI: 10.1093/jn/nxaa143
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Oxygenase 1 Activity Modulates Circulating Cholesterol Concentrations in Mice and Humans

Abstract: Background Plasma cholesterol is one of the strongest risk factors associated with the development of atherosclerotic cardiovascular disease (ASCVD) and myocardial infarction. Human studies suggest that elevated plasma β-carotene is associated with reductions in circulating cholesterol and the risk of myocardial infarction. The molecular mechanisms underlying these observations are unknown. Objective The objective of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…In our clinical study, subjects carrying at least one copy of the BCO1 rs6564851-T allele, which increases BCO1 activity (40), showed a reduction in total serum cholesterol and non-HDL-C concentrations. Similarly, we observed that wild-type mice fed WD-β-carotene presented a decrease in total cholesterol and non-HDL-C concentrations in comparison to congenic Bco1 -/mice subjected to the same dietary regimen (10). These studies raised the question as to what mechanism underlies this association and whether these alterations in circulating cholesterol have a clinical significance.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…In our clinical study, subjects carrying at least one copy of the BCO1 rs6564851-T allele, which increases BCO1 activity (40), showed a reduction in total serum cholesterol and non-HDL-C concentrations. Similarly, we observed that wild-type mice fed WD-β-carotene presented a decrease in total cholesterol and non-HDL-C concentrations in comparison to congenic Bco1 -/mice subjected to the same dietary regimen (10). These studies raised the question as to what mechanism underlies this association and whether these alterations in circulating cholesterol have a clinical significance.…”
Section: Discussionmentioning
confidence: 52%
“…We recently described an association between BCO1 activity and circulating cholesterol in mice and humans (10). In our clinical study, subjects carrying at least one copy of the BCO1 rs6564851-T allele, which increases BCO1 activity (40), showed a reduction in total serum cholesterol and non-HDL-C concentrations.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Estimation of the bioavailability of dietary provitamin A carotenoids based on dietary intake data and concentrations in blood has several limitations, the most relevant probably being the disparity in the dietary intake assessment methods and FCT (referred to above), and the fact that it is impossible to estimate their conversion into retinol in the human intestine and other tissues. The extent of this conversion varies widely among individuals, depending on diverse host related factors, such as the vitamin A nutritional status, the nucleotide polymorphisms (SNPs) within the b-carotene 15,15 -monoxygenase and specific binding proteins involved in their metabolism, presence of disease, seasonal variation in the food intake, sex, age and body mass index [12,14,[75][76][77]. Strengths of this study include the homogeneous characteristics of the subjects in our four studies with respect to (normal) cholesterolemia and to (adequate) retinol nutritional status.…”
Section: Discussionmentioning
confidence: 99%